Management Policy for Standardization of Physical Education Learning Infrastructure at the Elementary School Level in Langsa City, Indonesia - Nova, Andi; Syahputra, Muhajjir; Roberto, Julio; Surimeirian, Muhamad Anas; Nofrizal, Dedi (Universitas Majalengka, 2023)
This study analyzes the management policy of standardizing elementary school physical education learning infrastructure in 66 schools in 5 sub-districts of Se-Kota Langsa. This study aims to explore, find, and provide policy recommendations for standardizing infrastructure facilities to support effective learning. The implication is that if every elementary school has adequate infrastructure, it will impact the quality of learning. This approach uses qualitative policy research design. The study subjects were 66 elementary school principals, two from the education office, and local government. Data collection by observation, documentation, interviews, and literature studies. Data analysis uses data collection, data reduction, data display, conclusion drawing, and data validity by triangulation to find the validity of research data. The results of research from 66 elementary schools in Langsa City showed that only five schools met the standards, 61 schools did not meet the requirements, and the category was not feasible for infrastructure in terms of at least four aspects, namely the width of the infrastructure sector, building area, classrooms, and installations according to Permendiknas No. 24 of 2007 concerning learning infrastructure standards at the elementary level. From these four aspects, at least 61 schools located in narrow areas are not feasible to build standardized classrooms and sports infrastructure, at least multipurpose courts that can play badminton, volleyball, and mini soccer courts to support the learning activities of elementary school students. In contrast, five schools meet minimum standards and are fair. The impact of inadequate physical education infrastructure in 61 primary schools has been modified so that students are ineffective in learning.